Substrate‐Assisted Deposition of Metal Oxides on Three‐Dimensional Porous Reduced Graphene Oxide Networks as Bifunctional Hybrid Electrocatalysts for the Oxygen Evolution and Oxygen Reduction Reactions. Issue 17 (26th August 2016) - Zhao, Mengjia; Li, Xiaoxue; Song, Long; He, Di; Zhang, Zhipan
Abstract: The oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) are of great importance for energy conversion processes, such as water electrolysis, metal–air batteries, and fuel cells. Herein, we report a substrate‐assisted in situ reduction method to prepare three‐dimensional reduced graphene oxide (3DRGO) networks decorated with a range of mixed cobalt oxide and nickel oxide nanosheets as a new type of bifunctional catalyst for oxygen evolution and oxygen reduction. Among the different composite catalysts, Co3 O4 @3DRGO showed highest catalytic activities in OER and ORR with an excellent stability. This catalyst is used to catalyze the oxygen reactions in a Zn–air battery as a proof‐of‐concept. The current results render new insights into developing low‐cost, next‐generation bifunctional catalysts for photoelectrochemical cells for energy storage and conversion. Abstract : Bifunctional hybrid : An in situ reduction method is used to prepare 3D reduced graphene oxide (3DRGO) networks decorated with a range of mixed cobalt oxide and nickel oxide nanosheets as a new type of bifunctional catalyst for oxygen evolution and oxygen reduction. Overall, Co3 O4 @3DRGO shows the highest catalytic activities with an excellent stability and, as a proof‐of‐concept, this catalyst is used to facilitate the oxygen reactions in a Zn–air battery.